2004
DOI: 10.21273/jashs.129.2.0144
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Garlic Growth and Florogenesis

Abstract: An understanding of temperature and photoperiod effect on garlic (A. sativum L.) growth and florogenesis might solve the enigma of garlic sterility and provide environmental tools for flowering regulation and fertility restoration. The effect of storage temperature and growth conditions on the interactive relationships between the developing vegetative and reproductive organs was studied. A long photoperiod for more than 2 weeks was required for both dormancy induction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…Similar results have been observed in the case of a recombinant thermostable glutamate dehydrogenase (GDH) from a hyperthermophilic archaeon which was activated 2.6-fold upon heat treatment, i.e. 80 • C for 15 min [25]. It was observed that the heat treatment resulted in a reduction of the helical content of GDH along with the increase in the specific activity.…”
Section: Thermostabilitysupporting
confidence: 79%
“…Similar results have been observed in the case of a recombinant thermostable glutamate dehydrogenase (GDH) from a hyperthermophilic archaeon which was activated 2.6-fold upon heat treatment, i.e. 80 • C for 15 min [25]. It was observed that the heat treatment resulted in a reduction of the helical content of GDH along with the increase in the specific activity.…”
Section: Thermostabilitysupporting
confidence: 79%
“…The storage environment is a micro-climate which can further affect the composition of the bulb and cloves. While low temperatures promote the breaking of dormancy in garlic [11,16], garlic cultivars stored at 0 • C and 25 • C for eight weeks showed no significant differences in production of allicin, a breakdown product of alliin [17]. Cantwell et al [18], however, identified an increase in alliin, thiosulfinate and total pyruvate, all measures of flavour sources, in garlic stored at 0-1 • C for up to 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…During its domestication process, garlic began to lose its capacity to sexually reproduce, and seeds are not produced in the majority of current cultivars (Al‐Zahim et al , ; Volk et al , ). Viable seeds are only produced by some varieties from near of Centre of Origin (Hong & Etoh, ; Shemesh et al , ) and under specific environmental conditions (Kamenetsky et al , ; Shemesh et al , ). The current means of garlic propagation is vegetative, from cloves of harvested bulbs (Messiaen et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, not all cultivars completely develop an inflorescence, as many intermediate forms exist (in hard‐neck cultivars), or the apical bud may be substituted by a central clove (in soft‐neck cultivars). Although this is a genetic characteristic frequently used to classify plant material, distinct environmental conditions may noticeably modify the expression of a single cultivar (Kamenetsky et al , ). With regards to the formation and development of an inflorescence, Takagi () and Kamenetsky & Rabinowitch () claim that garlic types can be classified as one of the following: complete bolting, non‐bolting and incomplete bolting.…”
Section: Introductionmentioning
confidence: 99%